Career planning of undergraduate students of Ramkhamhaeng University - SUMANA CHARANASOMBOON (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: The study’s primary goal is to examine the role of Ramkhamhaeng University-RU, Thailand, in the career development of its undergraduate students. (2) to evaluate the pros and cons of various careers, and (3) to display the advice these deserving students give.Methodology: Four hundred undergraduates from the Schools of Law, Business, Humanities, Education, Science, Political Science, Economics, and Human Resource Development were randomly selected for this study. The data was gathered using a set of five rating scale questionnaires. The data was used to analyze the frequency, percentage, mean, standard deviation, t-test, and One-way ANOVA.Findings: As a result of this study, we know the following: (1) Students place a moderate amount of weight on their own interests and social considerations when making career decisions. Still, more weight is given to family considerations. (2) In terms of career planning, students wanted to work before and after college; (3) When comparing factors for students to choose their careers, the opinions of the students who differed in sex, fathers’ education and occupation, and students’ employment status showed concurrent differences at the statistically significant level of Last but not least, (4) about suggestions for undergraduate career planning, the university should offer more activities to help students get ready for career planning.Novelty/Implications: Planning a career, deciding on a career path, and building one’s career are all pivotal moments in a person’s life that last a lifetime. This research has explored these factors and provided helpful insights that benefit students, educators, and policymakers.